Architecture in the landscape: the architectural project from a sense of place - Cuadrado Torres, Holger Patricio (Artes: Architecture, Technology and Sustainability, 2025)
Awareness of place in the design process involves a sensitive and objective approach to the context in which the project is developed, serving as the foundation for the conception of contextualized architectural works. Incorporating this approach into architectural education strengthens critical thinking, enabling a responsible and objective stance regarding the relationship between the built work and its location. The landscape, as an essential component of place, is a key element in the formulation of architectural projects that are sensitive to their surroundings. Its proper interpretation generates architectural environments that foster harmonious relationships both outside and within inhabited spaces. Through literature review and case analysis, four design principles or approaches are identified, stemming from a sensitive interpretation of the landscape in which they are situated.